Review of Overseas Shinto Shrines. Religion, Secularity and Japanese Empire by Karli Shimizu, London, New York, Dublin: Bloomsbury, 2023. Xii + 278. - Skowron, Aleksandra (Silva Iaponicarum, 2024)
Review of Overseas Shinto Shrines. Religion, Secularity and Japanese Empire by Karli Shimizu, London, New York, Dublin: Bloomsbury, 2023. Xii + 278.